Q. 94.3( 14 Votes )

# Find each of the following products:

(x^{2} – y^{2}) × (x + 2y)

Answer :

By using horizontal method,

We have;

= (x^{2} – y^{2}) × (x + 2y)

= x^{2} (x + 2y) – y^{2}(x + 2y)

= x^{3} + 2x^{2}y – xy^{2} – 2y^{3}

Rate this question :

On dividing p (4p2 – 16) by 4p (p – 2), we get

NCERT - Mathematics ExemplarExpress each of the following prducts as a monomials and verify the result in each case for x=1:

Evaluate when a=1 and b = 0.5

RD Sharma - MathematicsState whether the statements are true (T) or false (F).

(9x – 51) ÷ 9 is x – 51.

NCERT - Mathematics ExemplarFind each of the following products:

RD Sharma - Mathematics

Express each of the following products as a monomials and verify the result for x=1, y= 2:

RD Sharma - Mathematics

The value of (3x^{3} + 9x^{2} + 27x) ÷ 3x is

Find each of the following products:

RD Sharma - Mathematics

Find each of the following products:

(9x^{2} – x + 15) × (x^{2} – x – 1)

Find each of the following products:

(x^{2} – 5x + 8) × (x^{2} + 2)